Characterization of CD166 from Nile tilapia (Oreochromis niloticus) displays a broad pathogen recognition spectrum and involved the immune response to microbial aggression. Issue 134 (March 2023) - Wang, Zhiwen; Xie, Caixia; Li, Yuan; Wang, Bei; Jian, Jichang; Lu, Yishan; Xia, Liqun; Chang, Mingxian
Abstract: CD166 is a member of the immunoglobulin superfamily of cell adhesion molecules, and its mediated adhesion plays a crucial role in different physiological and pathological phenomena, especially related to leukocyte extravasation, immune synapse stability, T cell activation and proliferation. In this study, CD166 was identified from Nile tilapia ( Oreochromis niloticus, OnCD166 ). OnCD166 contains an open reading frame of 1671 bp that encodes a peptide of 556 amino acids, and contains five consecutive extracellular immunoglobulin domains. It's tissue distribution and expression patterns after S. agalactiae challenge were also investigated. OnCD166 is widely distributed in various tissues of healthy tilapia. After Streptococcus agalactiae challenge, OnCD166 expressions were significantly up-regulated in all tested immune tissues. Meanwhile, the recombinant OnCD166 (rOnCD166E) protein showed strong agglutinating activities against both Gram-negative bacteria and Gram-positive bacteria. Moreover, rOnCD166E could promote phagocytosis of macrophages. Taken together, our results illustrated that OnCD166 might as a receptor involved in the immune recognition and phagocytosis against invading pathogen, which play important roles in the immune responses of Nile tilapia against bacterial pathogens. Highlights: OnCD166 was identified from Nile tilapia, Oreochromis niloticus. OnCD166 was mainly expressed in immune tissues and induced by the challenge of S. agalactiae. OnCD166 exhibited binding activities to a wide spectrum of microbes and PAMPs. OnCD166 might as a receptor involved in the immune recognition and phagocytosis against invading pathogen.